Hubungan Kecerdasan Matematis Logis Di Era Milenial Terhadap Hasil Belajar Fisika - Sulami Sibua; Dewi Mufidatul Ummah; Astuti Salim (Kappa Journal, 2021)
This study aims to determine the effect of logical mathematical intelligence on physics learning outcomes for class X students at SMAN 5 Ternate City. The method used is a quantitative method and is included in the type of case study research. The research subjects were students of class X SMAN 5 Ternate City who were selected randomly. Data analysis using tests and non-tests with 10 questions for physics learning achievement test instruments and IST intelligence test instruments for Computing Series (ZR) and Numerical (RA) Sub-Tests on the IST Test developed by LP3UI (Institute for the Study and Development of Applied Psychology at the University Indonesia), each of which consists of 20 statement items. The data analysis technique in this study used the SPSS 16.0 application, namely by testing the prerequisites and hypotheses. The results of his research show that the correlation coefficient (rxy) between logical mathematical intelligence and physics learning achievement is 0.439 and a significance of 0.000 < 0.5. Thus, H0 is accepted so that it can be concluded that "There is a positive relationship between intrapersonal intelligence and physics learning achievement for students  SMAN 5 Ternate City”